2021
DOI: 10.1101/2021.09.12.21263386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative study of Bacterial culture isolates, site of infections and drug resistance pattern between COVID and non COVID patients admitted in a tertiary care hospital: A Pilot study

Abstract: Introduction: SARS-CoV2 which is a corona virus also predisposes patient to secondary bacterial infection by various mechanisms like- damaging the respiratory epithelium, profoundly affecting the innate and adaptive immunity, antagonising Interferon responses that enhance bacterial adherence, colonisation and invasion to respiratory tissue. In addition, prolonged hospital stay, invasive therapeutic devices, widespread use of empiric antibiotics and most importantly use of immune-suppressants like Steroid or To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…Halder A et al 11 found that the Klebsiella was the most common organism in patients with COVID-19 and this finding is similar to the finding of the present study where we found that Klebsiella was the common isolate. They reported isolates of Acinetobacter in few cases.…”
Section: Discussionsupporting
confidence: 93%
“…Halder A et al 11 found that the Klebsiella was the most common organism in patients with COVID-19 and this finding is similar to the finding of the present study where we found that Klebsiella was the common isolate. They reported isolates of Acinetobacter in few cases.…”
Section: Discussionsupporting
confidence: 93%